Pituitary Action of E2 in Prepubertal Grass Carp: Receptor Specificity and Signal Transduction for Luteinizing Hormone and Follicle-Stimulating Hormone Regulation - Qin, Xiangfeng; Xiao, Yaqian; Ye, Cheng; Jia, Jingyi; Liu, Xiangjiang; Liang, Hongwei; Zou, Guiwei; Hu, Guangfu (Frontiers in Endocrinology, 2018)
17β-estradiol (E2) is an important sex steroid produced by ovary and brain. In mammals, E2 plays an important role in hypothalamus–pituitary–gonad axis to regulate puberty onset, however, little is known about the functional role of E2 in teleost pituitary. Using prepubertal grass carp as model, three nuclear estrogen receptors (nERs: estrogen receptor alpha, estrogen receptor beta 1, and estrogen receptor beta 2) and two G protein-coupled estrogen receptors (GPER1: GPER1a and GPER1b) were isolated from grass carp pituitary. Tissue distribution analysis indicated that both nERs and GPERs were highly detected in grass carp pituitary, which suggested that E2 should play an important role in grass carp pituitary. Using primary cultured grass carp pituitary cells as model, high-throughput RNA-seq was used to examine the E2-induced differentially expressed genes (DEGs). Transcriptomic analysis showed that E2 could significantly upregulate the expression of 28 genes in grass carp pituitary cells, which were characterized into different functions including reproduction, gonad development, and central nervous system development. Further studies confirmed that E2 could induce luteinizing hormone (LH) and follicle-stimulating hormone (FSH) secretion and mRNA expression in prepubertal grass carp pituitary in vivo and in vitro. In the pituitary, LH and FSH regulation by E2 were mediated by both ERβ and GPER1. Apparently, E2-induced LHβ and FSHβ mRNA expression were mediated by adenylyl cyclase/cAMP/protein kinase A, phospholipase C/inositol 1,4,5-triphosphate/protein kinase C, and Ca2+/calmodulin/CaM-dependent protein kinase II pathways. In addition to LH and FSH, E2 could also induce growth regulation by estrogen in breast cancer 1 (a novel regulator for pituitary development) mRNA expression in grass carp pituitary cells. These results, as a whole, suggested that E2 could play an important role in gonadotropin hormone release and pituitary development in prepubertal grass carp.